Effects of FP15, a peroxynitrite decomposition catalyst on cardiac and pulmonary function after cardiopulmonary bypass - Radovits, Tamás; Beller, Carsten J.; Karck, Matthias; Szabó, Gábor (European journal of cardio-thoracic surgery, 2012)
OBJECTIVE: Peroxynitrite, a toxic nitrogen species, has been implicated in the development of ischemia/reperfusion injury. The aim of the present study was to investigate the effects of the potent peroxynitrite decomposition catalyst, FP15, on myocardial, endothelial, and pulmonary function in an experimental model of cardioplegic arrest and extracorporal circulation. METHODS: Twelve anesthetized dogs underwent hypothermic cardiopulmonary bypass. After 60 min of hypothermic cardiac arrest, reperfusion was started and either saline vehicle (control, n = 6) or FP15 (n = 6) was administered. Left-ventricular preload-recruitable stroke work (PRSW) was measured by a combined pressure–volume conductance catheter at baseline and after 60 min of reperfusion. Left anterior descending (LAD) coronary (CBF) and pulmonary blood flow (PBF), endothelium-dependent vasodilatation to acetylcholine (ACh), and alveolo–arterial O2 gradient were determined. RESULTS: The administration of FP15 led to a significantly better recovery of PRSW (given as percent of baseline: 93 ± 9 vs 62 ± 6%, p < 0.05). CBF was also significantly higher in the FP15 group (44 ± 6 vs 25 ± 4 ml min−1, p < 0.05). Injection of ACh resulted in a significantly higher increase in CBF (70 ± 6 vs 35 ± 5%, p < 0.05) in the FP15-treated animals. The alveolo–arterial O2 gradient was significantly lower after FP15 administration (83 ± 7 vs 49 ± 6 mmHg, p < 0.05). Catalytic peroxynitrite decomposition did not affect baseline cardiovascular and pulmonary functions. CONCLUSIONS: Application of FP15 improves myocardial, endothelial, and pulmonary function after cardiopulmonary bypass with hypothermic cardiac arrest. The observed protective effects imply that catalytic peroxynitrite decomposition could be a novel therapeutic option in the treatment of ischemia/reperfusion injury.